2015
DOI: 10.1186/s13073-015-0209-4
|View full text |Cite
|
Sign up to set email alerts
|

Omic personality: implications of stable transcript and methylation profiles for personalized medicine

Abstract: BackgroundPersonalized medicine is predicated on the notion that individual biochemical and genomic profiles are relatively constant in times of good health and to some extent predictive of disease or therapeutic response. We report a pilot study quantifying gene expression and methylation profile consistency over time, addressing the reasons for individual uniqueness, and its relation to N = 1 phenotypes.MethodsWhole blood samples from four African American women, four Caucasian women, and four Caucasian men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Such individualization is reminiscent of our findings in healthy individuals [ 36 ]. In that study, we found, by contrasting the RNAseq profiles of a dozen of individuals at three six-month intervals, that all subjects consistently clustered together, whether considering the major PC of the entire transcriptome or the Axis scores.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Such individualization is reminiscent of our findings in healthy individuals [ 36 ]. In that study, we found, by contrasting the RNAseq profiles of a dozen of individuals at three six-month intervals, that all subjects consistently clustered together, whether considering the major PC of the entire transcriptome or the Axis scores.…”
Section: Discussionsupporting
confidence: 71%
“…In that study, we found, by contrasting the RNAseq profiles of a dozen of individuals at three six-month intervals, that all subjects consistently clustered together, whether considering the major PC of the entire transcriptome or the Axis scores. This gave rise to the notion of an “omic personality”, a consistent profile of gene expression over time that reflects the baseline healthy status of an individual [ 36 ]. This baseline expression is quite likely to have a major influence on the recovery profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Blood Transcript Module and BIT axis analyses, both based on comprehensive analysis of existing whole blood gene expression datasets, confirm that these types broadly reflect differences in gene activity in the major immune sub-types, partly reflecting cell abundance, but also innate states of activity of biosynthetic, cell cycle, and cytokine signaling. Immunoprofiling by flow cytometry has established that individuals have baseline profiles, or omic personalities [ 71 ], to which they return after immunological perturbation but which are also influenced by such environmental factors as child-rearing [ 72 ]. Sub-type-specific blood gene expression should be seen in light of this immunological elasticity, as the heterogeneity among subjects may be more meaningful for disease risk than individual eQTL effects.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the proportions of adipose and blood cell types in the adipose biopsies from the FUSION and METSIM studies, a reference transcriptome was created using RNA-Seq of whole blood (GEO accession GSE67488 54 ), and of four types of purified adipose cells (adipocytes, macrophages, CD4+ T cells, and microvascular endothelial cells) described in Glastonbury et al 33 . For the FUSION study, reference transcriptome reads were aligned to the hg19 reference genome using the same read mapping and quality control procedure as used for the FUSION adipose RNA-Seq data 27 .…”
Section: Methodsmentioning
confidence: 99%